Esophageal physiology—an overview of esophageal disorders from a pathophysiological point of view. Issue 1 (10th July 2020) - Lottrup, Christian; Khan, Abraham; Rangan, Vikram; Clarke, John O.
Abstract: The esophagus serves the principal purpose of transporting food from the pharynx into the stomach. A complex interplay between nerves and muscle fibers ensures that swallowing takes place as a finely coordinated event. Esophageal function can be tested by a variety of methods, endoscopy, manometry, and reflux monitoring being some of the most important. Regarding pathophysiology, motor disorders, such as achalasia, often cause dysphagia and/or chest pain. Functional esophageal disorders are a heterogeneous group with hypersensitivity as a dominant pathophysiological factor. Gastroesophageal reflux disease often causes symptoms, such as heartburn and regurgitation, and a spectrum of disease, ranging from minimal mucosal damage visible only in the microscope to esophageal ulcers and strictures in the most severe cases. Eosinophilic esophagitis is an immune‐mediated condition that can result in significant dysphagia and associated luminal narrowing. In the following, we will provide an overview of the most common esophageal disorders from a combined pathophysiological and clinical view. Abstract : Gastroesophageal reflux disease often causes symptoms such as heartburn and regurgitation and a spectrum of disease, ranging from minimal mucosal damage visible only in the microscope to esophageal ulcers and strictures in the most severe cases. Eosinophilic esophagitis is an immune‐mediated condition that can result in significant dysphagia and associated luminal narrowing. In the following, we will provide an overview of the most common esophageal disorders from a combined pathophysiological and clinical view.